Candida albicans adherence to an acrylic resin modified by experimental photopolymerised coatings: An in vitro study - Lazarin, Andrea Azevedo; Zamperini, Camila Andrade; Vergani, Carlos Eduardo [UNESP]; Wady, Amanda Fucci; Giampaolo, Eunice Teresinha; Machado, Ana Lucia [UNESP] (Wiley, 2012)
Purpose: This study evaluated whether photopolymerised coatings containing zwitterion or hydrophilic monomers would reduce the adhesion of Candida albicans to an acrylic resin. Materials and methods: Disc-shaped samples (n = 468) were fabricated with rough or smooth surfaces. The samples did not receive any surface treatment (control) or were coated with one of the following experimental coatings (2-hydroxyethyl methacrylate - HE; 3-hydroxypropyl methacrylate - HP; and 2-trimethylammonium ethyl methacrylate chloride - T; and sulfobetaine methacrylate - S). The concentrations of the constituent monomers were 25, 30 or 35%. The water contact angles of the samples were measured, and half of the samples were exposed to saliva. The adherent yeast cells were counted after crystal violet staining. Results: For the smooth samples, the groups S35, HP35 and HE35 showed significantly lower number of adhered Candida than control, in the absence of saliva. There were no significant differences among the experimental and control groups for the rough samples, but the saliva decreased the cell numbers for groups S25, S30 and HP30. The photoelectron spectroscopy analysis confirmed the changes in the chemical compositions of the experimental samples. Conclusions: The experimental photopolymerised coatings changed the chemical composition and decreased C. albicans adhesion in the groups S35, HP35 and HE35, suggesting that they should be further investigated. © 2012 The Gerodontology Society and John Wiley & Sons A/S.
Keywords: Acrylic resin; Biofilm; Candida; Saliva